Workshop Internet of Things (IoT) - Farindika Metandi; Damar Nurcahyono; Abdul Najib (Universitas Muhammadiyah Magelang, 2022)
SMK Negeri 7 Samarinda aspires to be a world-class information and communication technology school. It is important for students to understand about technology advancements in order to become employable human resources in the workplace. Teachers' roles in schools are critical in helping students learn this, hence vocational school teachers should have Internet of Things (IoT) training. The workshop will take place entirely online, utilizing Google Meet. Following the training, it can be inferred that partners will have a simple understanding of the IoT technology work system, particularly when the pilot is deployed. Partners can learn and grasp the notion of blended learning models with IoT through workshops and facilities.